Tinjauan Pustaka: Dwarfisme pada Anjing - I Kadek Restu Saputra (JURNAL RISET RUMPUN ILMU HEWANI, 2025)
Canine dwarfism is a growth disorder resulting from physiological dysfunction within the endocrine system, primarily due to growth hormone (GH) deficiency commonly caused by abnormal pituitary development. GH and Insulin-like Growth Factor 1 (IGF-1) play essential roles in regulating the growth of bones, muscles, skin, and internal organs through the hypothalamic–pituitary–liver axis. Under normal conditions, the hypothalamus controls GH secretion, which subsequently stimulates the liver to produce IGF-1 as the main mediator of growth. Genetic abnormalities such as LHX3 mutations can impair somatotroph cell differentiation and reduce GH production, ultimately leading to decreased IGF-1 levels. The deficiency of these hormones disrupts chondrocyte proliferation in the epiphyseal plates, decreases muscle protein synthesis, and negatively affects the development of tissues such as skin, hair, and reproductive organs. This study was conducted using a literature review method by searching scientific databases and selecting relevant publications addressing the physiological, clinical, and pathophysiological aspects of canine dwarfism. Literature analysis indicates that GH deficiency leads to clinical manifestations such as stunted body size, thin and easily shedding hair, dry and infection-prone skin, reduced muscle mass, metabolic disturbances, and delayed reproductive maturation. Diagnosis is established through clinical evaluation, IGF-1 measurement as an indicator of GH activity, and radiographic assessment of epiphyseal plate development. Overall, a comprehensive understanding of the relationship between physiological abnormalities and clinical signs is crucial for early detection and appropriate management of dwarfism, providing a strong scientific foundation for understanding the hormonal mechanisms disrupted in this condition.